Control strategy of harmonic suppression of micro-grid based on virtual harmonic impedance - XU Ruidong; ZHOU Jianyong; WANG Boya; YU Zhiwei; WANG Linge; CAO Liru; WU Chenli (Gong-kuang zidonghua, 2017)
In view of problem of harmonic pollution caused by nonlinear loads in micro-grid, a control strategy of harmonic suppression of micro-grid based on virtual harmonic impedance was proposed. The principle of droop control is analyzed, and harmonic suppression model of two inverters running in parallel is given. The harmonic current is detected by SOGI model and voltage zero-steady-state error control is achieved by improved PR quasi-proportional resonant controller based on SOGI model. The virtual harmonic impedance control strategy and its implementation are analyzed. The simulation and experimental results verify correctness and reliability of the control strategy.